2016
DOI: 10.1051/matecconf/20165702012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Code Refactoring Impact on Software Quality

Abstract: Abstract. Code refactoring is a "Technique used for restructuring an existing source code, improving its internal structure without changing its external behaviour". It is the process of changing a source code in such a way that it does not alter the external behaviour of the code yet improves its internal structure. It is a way to clean up code that minimizes the chances of introducing bugs. Refactoring is a change made to the internal structure of a software component to make it easier to understand and chea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…As a result, the use of these tools sometimes negatively affects the quality of the code [34]. For example, Kaur and Kaur [51] used the Miner refactoring tool and found that the Move Method increased complexity. On the other hand, Chavez et al [52] used JDeodorant tool to apply this refactoring and found that the Move Method did not affect complexity.…”
Section: B Different Effects Of Refactoring Techniquesmentioning
confidence: 99%
“…As a result, the use of these tools sometimes negatively affects the quality of the code [34]. For example, Kaur and Kaur [51] used the Miner refactoring tool and found that the Move Method increased complexity. On the other hand, Chavez et al [52] used JDeodorant tool to apply this refactoring and found that the Move Method did not affect complexity.…”
Section: B Different Effects Of Refactoring Techniquesmentioning
confidence: 99%
“…44 By refactoring code smells, we can improve the code quality in terms of reduction in complexity and maintenance cost. 45 Every code smell has its refactoring solution. 11 For example, Long Method code smell can be solved by using Extract Method refactoring, 46,47 Duplication in two unrelated classes can be solved using Extract Component, 27 and Shotgun Surgery, Feature Envy, Inappropriate Intimacy use Move Method and Move Field refactoring techniques.…”
Section: Alternative Classes With Different Interfacesmentioning
confidence: 99%
“…It cleans the code and makes it simple and readable 44 . By refactoring code smells, we can improve the code quality in terms of reduction in complexity and maintenance cost 45 . Every code smell has its refactoring solution 11 .…”
Section: Background and Related Workmentioning
confidence: 99%
“…Code refactoring is the technique that restructures the code without changing its semantic behaviors [23], [24]. The initial purpose of code refactoring is to improve readability and reduce code complexity.…”
Section: B Code Refactoringmentioning
confidence: 99%